Pemanfaatan Pupuk Sapi Kandang dan Pupuk Cair Organik Kulit Pisang Untuk Meningkatkan Pertumbuhan dan Produksi Jagung Manis (Zea mays L. saccharata Sturt) - Ahmad Sofian; Nuraida Nuraida; Daniel Steven Tumanggor (Universitas Islam Raden Rahmat, Malang, 2024)
Sweet corn (Zea mays L. saccharata Sturt) is one type of annual crop whose life cycle is only 80 - 150 days. This study aims to determine the growth and production of sweet corn (Zea mays L. saccharata Sturt) due to the application of cow manure and banana peel liquid organic fertilizer. This research was conducted from March to July 2023. This study used a Factorial Randomized Group Design with 2 factors studied and 3 replications where the first factor was cow manure (K) consisting of 3 levels, namely K0 = 0 tons/ha (control), K1 = 15 tons/ha, K2 = 30 tons/ha. The second factor is banana peel liquid organic fertilizer (P) which consists of 4 levels, namely P0 = 0% (control), P1 = 10% / 1 litre of water, P2 = 20% / 1 litre of water, P3 = 30% / 1 litre of water. The results showed that the application of cow manure had a very significant effect on the parameters of plant height, leaf area, length of husked cob, diameter of husked cob and weight of husked cob per sample and had a significant effect on weight of husked cob per plot. The application of banana peel liquid organic fertilizer has a significant effect on the diameter of the husked cob but had no significant effect on the parameters of plant height, leaf area, length of husked cob, weight of husked cob per sample and weight of husked cob per plot. The interaction between cow manure and banana peel liquid organic fertilizer had no significant effect on all parameters observed.